Understanding Online Consumptive Behavior Among Students: The Impact Of Literacy, Lifestyle, And Digital Payment Adoption - Moch. Najwan Muzakky; Lela Hindasah (Indonesian Journal of Innovation Multidisipliner Research, 2026)
This study examines the impact of financial literacy, digital literacy, lifestyle, and digital payment usage on online consumptive behavior among university students. Using a quantitative approach, data were collected from 181 students through purposive sampling and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The analysis includes outer model evaluation, inner model assessment, and hypothesis testing. The results reveal that financial literacy and digital literacy have a significant negative effect on consumptive behavior, indicating that higher levels of literacy reduce excessive online spending. In contrast, lifestyle and digital payment usage exhibit a significant positive effect, suggesting that modern lifestyle patterns and the ease of digital transactions encourage consumptive tendencies. These findings highlight the dual role of literacy and digital financial tools in shaping consumer behavior in the digital era. This study contributes to the literature by providing empirical evidence on the behavioral consequences of digitalization among young consumers.